Thermal disruption of the food matrix of biofortified lettuce varieties modifies absorption of carotenoids by Caco-2 cells. (5th March 2020) - de Oliveira, Cleiton Lourenço; Brychkova, Galina; Esteves-Ferreira, Alberto Abrantes; McKeown, Peter; de Souza Gomes, Matheus; Maluf, Wilson Roberto; Gomes, Luiz Antonio Augusto; Spillane, Charles
Abstract: Amongst green leafy vegetables, new varieties of lettuce enriched in lutein and β-carotene are being developed to provide increased supply of dietary carotenoids. We investigated the effect of lettuce genotypes (varieties) and thermal treatments on lutein and β-carotene bioaccessibility to the micellar fraction (and also carotenoid bioavailability) using a human Caco-2 cell model system. Carotenoid absorption by mammalian cells is not correlated with initial carotenoid concentration in fresh lettuce leaves. While thermal treatment of lettuce leaves increases carotenoid availability, resulting in higher lutein and β-carotene absorption, disruption of the food matrix by prior cooking results in reduced carotenoid levels and transfer to the micellar fraction. Unless the food matrix is disrupted through breeding or post-harvest treatments, absorption of carotenoids from biofortified lettuce remains similar to lettuce cultivars with low carotenoid levels. Genetic improvement programs for biofortified lettuce varieties need to focus on increasing the carotenoid bioavailability from the food matrix. Highlights: Biofortified lettuce varieties are being developed with higher levels of carotenoids. Carotenoid absorption by human cells is not correlated with carotenoid levels in leaves. Thermal treatment of lettuce leaves increases carotenoid availability. Disruption of food matrix by cooking results in reduced carotenoid levels. Lettuce biofortification must increase carotenoid bioavailability from food matrix.